Neural unit element application for in use microwave circuitry - Caglar, M. Fatih; Gunes, Filiz (SPRINGER-VERLAG BERLIN, 2006)
In this work, a Neural Unit Element (NUE) is defined to be used in the analysis and synthesis of the microwave circuits. For this purpose, analysis of impedance transformation property of a transmission line segment with the parameters (B-l, Z(0)) is defined as the problem in the forward direction and synthesis of the transmission line to obtain the target impedance is also defined the problem in the reverse direction. This problem is solved using Multilayer Perceptron (MLP) with efficient training algorithm. Finally, NUE driven by 50 Omega and complex source which is very common in microwave applications and the short-circuited NUE (Stub) are given as the worked examples.
Keywords: NETWORK MODEL; Computer Science